The NIN Transcription Factor Coordinates Diverse Nodulation Programs in Different Tissues of the Medicago truncatula Root. Issue 12 (15th December 2015) - Vernié, Tatiana; Kim, Jiyoung; Frances, Lisa; Ding, Yiliang; Sun, Jongho; Guan, Dian; Niebel, Andreas; Gifford, Miriam L.; de Carvalho-Niebel, Fernanda; Oldroyd, Giles E.D.
Abstract : The Medicago truncatula transcription factor NIN coordinates diverse processes during nodulation, restricting ENOD11 expression in the root epidermis and promoting CRE1 expression in the root cortex. Abstract: Biological nitrogen fixation in legumes occurs in nodules that are initiated in the root cortex following Nod factor recognition at the root surface, and this requires coordination of diverse developmental programs in these different tissues. We show that while early Nod factor signaling associated with calcium oscillations is limited to the root surface, the resultant activation of Nodule Inception (NIN) in the root epidermis is sufficient to promote cytokinin signaling and nodule organogenesis in the inner root cortex. NIN or a product of its action must be associated with the transmission of a signal between the root surface and the cortical cells where nodule organogenesis is initiated. NIN appears to have distinct functions in the root epidermis and the root cortex. In the epidermis, NIN restricts the extent of Early Nodulin 11 ( ENOD11 ) expression and does so through competitive inhibition of ERF Required for Nodulation (ERN1). In contrast, NIN is sufficient to promote the expression of the cytokinin receptor Cytokinin Response 1 ( CRE1 ), which is restricted to the root cortex. Our work in Medicago truncatula highlights the complexity of NIN action and places NIN as a central player in the coordination of the symbiotic developmental programs occurring in differing tissues of the root that combined are necessary for a nitrogen-fixing symbiosis.